Adaptive output control of a mobile manipulator hanging from a quadcopter unmanned vehicle. (November 2019) - Ballesteros-Escamilla, Mariana Felisa; Cruz-Ortiz, David; Chairez, Isaac; Luviano-Juárez, Alberto
Abstract: This article summarizes the comprehensive design of an adaptive control that solves the trajectory tracking of a four-rotor unmanned aerial vehicle supplied by an own-designed grasping device. The controller design uses the regular proportional–derivative (PD) structure which is common to solve regulation, as well as tracking problems for robotic systems. The PD structure needs the estimation of the time-derivative to be exerted on-line. The super-twisting algorithm served to operate as a decentralized estimator of the derivatives for the tracking errors. The controller gains were adjusted by the differential laws aimed to track attainable reference trajectories. The adaptive strategy adjusts the controller gains enforcing the convergence of both the estimation and the tracking errors. A numerical example showed the observer/controller performance. A comparison with a classic non-adaptive PD controller confirms the effectiveness on the tracking task by the proposed design. In addition, a set of virtual numerical evaluations using the parameters of a real quadcopter system confirmed the performance benefits of the adaptive controller based on the PD structure aided with the estimation of the velocity obtained by the observer. Highlights: This study presents the design of an adaptive controller to solve a trajectory tracking problem. The tracking applies for a modified unmanned aerial vehicle supplied by a grasping device. The super twisting algorithm operated as a decentralized differentiator for the tracking errors. The controller gains were adjusted by a differential law aimed to track attainable reference trajectories. The adaptive gain strategy adjusts the controller gains enforcing the convergence of the tracking errors.